Deep history and beyond: a reply to commentators. (19th May 2023) - LeDoux, Joseph
ABSTRACT: The commentaries by Ren, de Carvalho, Gabriel, Reber and Baluška raise interesting and timely questions about the views I expressed in The Deep History of Ourselves. I begin my response with an Overview of my perspective, and how it has changed in the three years since publication. This is important since some of the commentators' concerns may be assuaged by some of these points. Other specific issues raised by each commentator are addressed separately. I greatly appreciate the time and effort they put into their comments on The Deep History of Ourselves.